BUSINESS GAME AS A COMPLEX INTERACTIVE TECHNOLOGY IN EDUCATION - Tasanova Evelina; Khamitov Eldorbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Lectures, seminars, laboratories, practical classes, and the business game develop highly talented experts. Students are engaged in games-based learning. Rethink our representations. Goal. This article examines business games and their potential to improve foreign language abilities in higher education. Methodology.